The relevance of intellectual capital in shared service centres: an exploratory research on the contribution of three models from different areas of knowledge - Domingues, L.; Pinto, A.; Carlos J. G. (International Journal of Technology and Human Interaction, 2018)
In the context of shared services, considering the intrinsic characteristics of the concepts service and sharing, organizational knowledge can assume different levels of relevance depending on the models adopted, from the most conventional to the most recent models considered as new forms of shared services. These are: Centres of Competence, Centres of Excellence, Centres of Expertise and Technical Centres. According to Nonaka, the creation of new knowledge takes place in a continuous process of transformation of tacit knowledge into explicit knowledge. Marciniak correlates the new models of shared services with the tacit and explicit knowledge. Domingues presents in the SSAM model the concept of intellectual capital as the driving force of innovation and quality service effectiveness. This article, using a qualitative approach and constructivist paradigm, develops exploratory research that aims in new directions and horizons at the confluence of these three models (Nonaka, SSAM and Marciniak) in knowledge management at shared service centres.